2020
DOI: 10.1007/s43440-020-00135-w
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of atorvastatin on cardiometabolic risk factors in brothers of women with polycystic ovary syndrome

Abstract: Background Women with polycystic ovary syndrome (PCOS) are characterized by increased cardiometabolic risk. The aim of the current study was to compare the impact of atorvastatin on plasma levels of cardiometabolic risk factors between men whose sisters had either PCOS or were unaffected. Methods The study population consisted of two age-, fat-free mass index-, blood pressure- and plasma lipid-matched groups of men with elevated total and LDL chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…In line with a previous study including normotensive men with elevated total and LDL cholesterol, 17 at the beginning of the study brothers of PCOS probands differed from male siblings of unaffected women in the severity of insulin resistance, plasma levels of androstenedione, and calculated bioavailable testosterone, as well as in levels of hsCRP and 25‐hydroxyvitamin D. Male siblings of women with PCOS were also characterized by a more atherogenic lipid profile. Our findings cannot be attributed to anthropometric differences and/or various blood pressure values because both study groups were matched for age, total and fat‐free mass index, and blood pressure.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In line with a previous study including normotensive men with elevated total and LDL cholesterol, 17 at the beginning of the study brothers of PCOS probands differed from male siblings of unaffected women in the severity of insulin resistance, plasma levels of androstenedione, and calculated bioavailable testosterone, as well as in levels of hsCRP and 25‐hydroxyvitamin D. Male siblings of women with PCOS were also characterized by a more atherogenic lipid profile. Our findings cannot be attributed to anthropometric differences and/or various blood pressure values because both study groups were matched for age, total and fat‐free mass index, and blood pressure.…”
Section: Discussionsupporting
confidence: 78%
“…Bioavailable testosterone is regarded as a better marker of androgen status in men than total testosterone and its precursor, 28 and therefore, despite no significant impact of telmisartan on total testosterone and androstenedione, this finding seems relevant. Previously, we reported that lower calculated bioavailable testosterone in brothers of women with PCOS was accompanied by increased dehydroepiandrosterone sulfate 17 . This observation indicates that male siblings of PCOS probands may be characterized by impaired conversion of dehydroepiandrosterone sulfate to testosterone.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Because of the exclusion criteria and selection procedure, these findings could not be attributed to differences in body mass index, blood pressure, plasma lipids, concomitant disorders, or drug interactions. The hormonal profile of individuals with early-onset alopecia differed from that observed in the male siblings of PCOS probands, in whom elevated concentrations of DHEA-S coexisted with lower levels of calculated bioavailable testosterone [ 17 ]. Unlike bioavailable testosterone, in both studies, mean total testosterone levels were similar to those observed in control groups.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a recent study indicated that cardiometabolic effects of atorvastatin are less pronounced in brothers of women with polycystic ovary syndrome than in the male siblings of unaffected women [ 17 ]. Moreover, high-dose treatment with rosuvastatin, the latest and the most potent statin that is currently available on the market and frequently used in clinical practice, was found to reduce circulating testosterone levels but not to affect levels of DHEA-S in men with coronary artery disease [ 18 ].…”
Section: Introductionmentioning
confidence: 99%